Structure characteristics of methane-doped solid normal hydrogen - Galtsov, N.N.; Prokhvatilov, A.I.; Strzhemechny, M.A. (Физика низких температур, 2000)
Structure studies of the quantum crystal of solid normal hydrogen doped with methane and deuteromethane are carried out by powder x-ray diffraction within the temperature range 5 to 12 K. The concentration of the dopants in the gas mixtures used for sample preparation by quench condensing is varied from 0.5% to 5%. It is established that the equilibrium solubility of both methanes is substantially below the lower fraction indicated. The abnormally high apparent extra volumes per impurity may be ascribed to van der Waals complexes formed around isolated dopant particles.